I dispersion in Argentina: Concentrations in fresh and marine water and deposition fluences in Patagonia - Negri, Agustin Eduardo; Fernandez Niello, Jorge Oscar; Wallner, Anton; Arazi, Andres; Fifield, Leslie K.; Tims, Stephen G. (American Chemical Society, 2013)
Fil: Negri, Agustin Eduardo. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina